Analisis Kontribusi Program Pospay Terhadap Pendapatan Pada Kantor Pos Prabumulih 31100 - Meiriani Betriana (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Every company is established to achieve certain goals, whether it's a company engaged in services, trade or industry. In general, the company's short-term goal is to obtain the maximum possible profit or profit. Meanwhile, the company's long-term goals are very diverse, including developing business and expanding networks so that the company can maintainits existence. To maintain its existence and to remain competitive in the business world, companies or entities rely on information technology systems. Pospay is one of the financial service products at PT. Posts that serve any bill payment. By using the Pospay service, people no longer have to bother paying multiple bills in different places. Because Pospay is now using an online system or SOPP (Online Payment Point System) which makes it easier for people to make payments without having to go to the Post. According to PT. Pos Indonesia (Persero) in the SOPP Pos Service Implementation Guidebook that the meaning of the Pos Online Payment Point System (SOPP) is an online payment service for paying accounts or bills of partners of PT. Indonesian post. This research generally aims to find out how the pospay program's contribution to income at the Prabumulih Post Office 31100. This type of research is a quantitative descriptive research, where the data used is quantitative data, namely income with secondary data sources obtained directly from the Prabumulih Post Office 31100. The data analysis technique used to determine the contribution of the Pospay program to the post office's income is to use the contribution formula, namely the contribution that one thing can give to another. The results of research in 2016 and 2017 income from the pospay program contributed 26.15% and 26.87% with moderate assessment criteria. Meanwhile, in 2015, 2018 and 2019 the achievement of income contribution from the pospay program reached a fairly good assessment criteria, namely 32.63% for 2015, 32.60% for 2018 and 32.97% in 2019. Keywords: Pospay, Income.